Filial Experiences and Challenges of Caregivers of the Individuals with Tourette Syndrome - Bautista, Aileen C. (Animo Repository, 2024)
Tourette Syndrome (TS) is a neurological condition that has physically and psychologically affected individuals afflicted with this condition. Their health situation has an impact on their families’ lives. In this case study, we aimed to examine the various experiences of the family members of the individuals with TS. Informed by the postulations of Ramanathan (2010) and Rivera-Navarro et al. (2014), we interviewed parents and siblings of individuals diagnosed with TS. Through these interviews, our study revealed that family members share the struggles of individuals with TS in dealing with and managing their conditions. They also shared some of their perceptions about having a life of normalcy despite living with family members with TS. Furthermore, dealing with the realities of living with them with this kind of condition has opened up a greater understanding of their physiological makeup. Finally, parents expressed the need for various agencies to extend their support to groups like them in achieving their full potential as individuals.